Effects of within-field and landscape factors on Dasineura brassicae in winter oilseed rape cultivations in Skåne, southern Sweden - Johansson, Emma (2019)
Winter oilseed rape (Brassica napus) is the most common oilseed crop grown in the province of Skåne in southern Sweden, where this study was performed. B. napus is often associated with various insect pests. This study regards two of these; the cabbage seed weevil (Ceutorhynchus obstrictus) and the brassica pod midge (Dasineura brassicae). While direct infestations by C. obstrictus usually do not pose a major threat to B. napus cultivations, the attacks will often facilitate infestation by D. brassicae, which can cause considerable damage and subsequent yield loss through its destruction of pods. This study focuses on within-field and landscape factors that may affect abundance and damage by D. brassicae in 18 rape fields during spring and summer of 2018. Parameters investigated include chemical treatment, abundance of C. obstrictus, landscape complexity (proportion of e.g. forested areas), the proportional area of oilseed rape grown in the previous year, and distance to the nearest previous years’ oilseed rape field. Effects of chemical treatments were assessed by establishing a pesticide-free control zone in each of the study fields. Samples were collected for nearly 10 weeks from April to July. Two field surveys of pod damages were performed during this period; the first during early pod set and the second during late pod set.